Cigarette smoking and bone mineral density in the elderly. Issue 1 (February 1996) - Egger, P; Duggleby, S; Hobbs, R; Fall, C; Cooper, C
Abstract : OBJECTIVE: To test the hypothesis that cigarette smoking is associated with reduced bone mineral density in elderly men and women. DESIGN: Cross sectional study. SUBJECTS: These comprised 224 men and 186 women aged 61-73 years, born and resident in East Hertfordshire. MEASUREMENTS: Lumbar spine and femoral neck bone mineral density (BMD) were determined by dual energy x ray absorptiometry. RESULTS: After adjusting for potential confounding variables, men who were current smokers were found to have a lumbar spine BMD that was 7.3% (95% CI 0.4, 14.2) lower than men who had never smoked. Similarly, women who were current smokers had a BMD value that was 7.7% (95% CI 0.3, 15.6) lower than in women who had never smoked. The difference at the femoral neck was smaller and not statistically significant. For both men and women, each decade of smoking was associated with a reduction of 0.015 g/cm2 in BMD at the lumbar spine (95% CI: men 0.002, 0.027; women 0.003, 0.028). At the femoral neck the reduction in BMD was 0.011 g/cm2 (95% CI 0.003, 0.020) for men and 0.004 g/cm2 (95% CI -0.003, 0.012) for women with each decade of smoking. CONCLUSIONS: The results show an adverse effect of smoking on BMD which was most noticeable at the lumbar spine, and seemed stronger in men than women. This effect could not be explained by differences in life style between smokers and nonsmokers.